THU0540 A PHASE 2B STUDY OF INTRAVENOUSLY (IV) ADMINISTERED TC 99M TILMANOCEPT TO DETERMINE DIFFERENTIAL UPTAKE, REPRODUCIBILITY OVER TIME AND IMAGE STABILITY IN HEALTHY SUBJECTS AND IN PATIENTS WITH RHEUMATOID ARTHRITIS (RA) ON STABLE TREATMENT. (2nd June 2020) - Hussein, A.; Ralph, D.; Potter, B.; Abbruzzese, B.; Hershey, R.; Repp, K.; Shakhtra, H.; Goel, M.; Palmer, M.; Kissling, A.; Hartings, C.; Blue, M.; et al.
Abstract : Background: At present, there are no reliable noninvasive means to directly monitor disease activity in RA patients. Activated macrophages are a critical component of the inflammatory etiology of RA due to their role in prolonged RA joint inflammation and destruction through the release of pro-inflammatory cytokines and chemokines. Tc 99m tilmanocept is a radiopharmaceutical imaging agent that binds with high affinity to the macrophage mannose receptor CD206 that resides on activated macrophages. Previous clinical trials demonstrated safety and tolerability of Tc 99m tilmanocept, as well as a determination of optimal clinical dose and timeframe for RA imaging. Objectives: The current phase 2b study aims to evaluate reproducibility and stability of imaging and will assess quantitative Tc 99m tilmanocept uptake cut points that reliably enable discrimination between joints of healthy people and RA patients. Methods: The analysis cohort contained 18 healthy controls (HC) clinically free of inflammatory joint disease and 12 subjects with clinically diagnosed RA who are on stable anti-inflammatory and/or anti-rheumatic therapy. Each subject received a 150-mcg dose of tilmanocept radiolabeled with 10 mCi of Tc 99m in a 3mL IV injection. Injection was followed by planar imaging at 60 and 180 minutes for both HC and RA subjects on study Day 0 and repeated in RA subjects on Day 8. Images were quantitatively assessed to detect localization within synovial spaces of bilateral hands and wrists by determining average pixel intensity in each region of interest relative to average pixel intensity in a joint-specific reference region. Results: Data obtained from the interim analysis support the hypothesis that Tc 99m tilmanocept imaging can provide robust quantitative imaging in HC and RA subjects. Repeat images within and between days demonstrate root mean squared differences that are approximately 10% or less of the observed localization of Tc 99m tilmanocept. Qualitatively, images of HC indicated no disease-related site-specific localization, whereas localization is present in RA subjects at levels expected given the difference in macrophage number and density in different pathotypes of RA. Notably, images from patients with active RA exhibit the same localization patterns on images taken in a test-retest fashion on the same day as well as in subjects with images acquired on Day 0 and Day 8 (see Figure 1 ). These results show low imaging readout variability, enabling reliable quantification of joints with RA-involved macrophage-mediated inflammation. Analysis of the HC and RA images was used to determine initial quantitative "cut-points" to differentiate between joints with and without the inflammation typically seen in RA. Conclusion: Tc 99m tilmanocept imaging of the joints in healthy subjects as well as in patients with active RA under stable treatment is reproducible and stable over time. The results confirmed that the signal in joints of healthy subjects and RA patients can be quantified and used to establish cut points to distinguish inflamed and non-inflamed joints on a joint-by-joint basis. These results provide the foundation for a noninvasive, objective method to monitor activity in macrophage-driven inflammation in joints of patients with RA. Disclosure of Interests: Ayah Hussein Employee of: Currently employed by Navidea Biopharmaceuticals, David Ralph Consultant of: Previous consultant for Navidea Biopharmaceuticals, Employee of: Currently employed by Navidea Biopharmaceuticals, Beth Potter Employee of: Currently employed by Navidea Biopharmaceuticals, Bonnie Abbruzzese Employee of: Currently employed by Navidea Biopharmaceuticals, Rachael Hershey Employee of: Currently employed by Navidea Biopharmaceuticals, Katherine Repp Employee of: Previously employed by Navidea Biopharmaceuticals, Haya Shakhtra Employee of: Currently employed by Navidea Biopharmaceuticals, Mehak Goel Employee of: Currently employed by Navidea Biopharmaceuticals, Madison Palmer Employee of: Currently employed by Navidea Biopharmaceuticals, Allison Kissling Employee of: Previously employed by Navidea Biopharmaceuticals, Carley Hartings Employee of: Previously employed by Navidea Biopharmaceuticals, Michael Blue Employee of: Currently employed by Navidea Biopharmaceuticals, Michael Rosol Employee of: Currently employed by Navidea Biopharmaceuticals